A Study on the Mediating Role of Work-Family Conflict in the Effect of Workload Perception on Professional Burnout of Employees in the Energy Sector - Tuba Koşarsoy; Burcu Özgül (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
AbstractPrevious research could not yield consistent results concerning the relationship between workload perception and dimensions of professional burnout. The present work examines the mediating role of work-family conflict (WFC) in the relationship between workload perception and the dimensions of professional burnout (emotional exhaustion, depersonalization, and lack of personal accomplishment). The population of this study consists of employees employed in 21 electricity distribution companies operating in the energy sector in Turkey. 221 usable data were obtained through the survey method. The data were tested with the SmartPLS 4 analysis program. The analysis found a significant positive relationship between workload perception and emotional exhaustion, depersonalization, and WFC. However, no significant correlation between workload perception and lack of personal accomplishment could be identified. Moreover, the study results confirmed a significant positive relationship between WFC and the three dimensions of professional burnout. Considering the mediating relationships, it was revealed that WFC plays a complementary partial mediating role in the relationship between workload perception and emotional exhaustion and depersonalization. Likewise, the full mediating role of WFC in the relationship between workload perception and a lack of personal accomplishment was confirmed. This research contributes significantly to literature and practice by showing that lack of personal accomplishment develops when workload perception turns into WFC.